2007
DOI: 10.1111/j.1467-8543.2007.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

From Coping Strategies to Tactics: London's Low‐Pay Economy and Migrant Labour

Abstract: This article examines the means by which low-paid migrant workers survive in a rapidly changing and increasingly unequal labour market. In a departure from the coping strategies literature, it is argued that the difficulties migrant workers face in the London labour market reduces their ability to 'strategize'. Instead, workers adopt a range of 'tactics' that enable them to 'get by', if only just, on a day-to-day basis. The article explores these tactics with reference to the connections between different work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
165
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(169 citation statements)
references
References 72 publications
(91 reference statements)
3
165
0
1
Order By: Relevance
“…And how does this link to their lower levels of labour market power? Author et al (forthcoming) have noted the importance of researching the construct of the migrant work ethic, and in particular how this is linked to factors that affect labour market power, particularly portability of qualifications and English language proficiency (see also Datta et al, 2007). In the context of these highly qualified migrants often taking lower skilled roles as a result of lower levels of labour market power (Author et al, forthcoming), it has been noted by many previous studies that managers consistently point to migrants' higher levels of 'work ethic' (Mackenzie and Forde, 2009;Waldinger and Lichter, 2003) when taking these jobs.…”
Section: Labour Market Power and The 'Migrant Work Ethic'-a Regional mentioning
confidence: 99%
See 1 more Smart Citation
“…And how does this link to their lower levels of labour market power? Author et al (forthcoming) have noted the importance of researching the construct of the migrant work ethic, and in particular how this is linked to factors that affect labour market power, particularly portability of qualifications and English language proficiency (see also Datta et al, 2007). In the context of these highly qualified migrants often taking lower skilled roles as a result of lower levels of labour market power (Author et al, forthcoming), it has been noted by many previous studies that managers consistently point to migrants' higher levels of 'work ethic' (Mackenzie and Forde, 2009;Waldinger and Lichter, 2003) when taking these jobs.…”
Section: Labour Market Power and The 'Migrant Work Ethic'-a Regional mentioning
confidence: 99%
“…It shows that upon moving to the UK migrant workers have low levels of labour market power as a result of lack of portability of qualifications and lower levels of English language skills. This prevents these migrants from obtaining roles that better suit their wider skill sets (see also Datta et al, 2007). As they move into low skilled and often temporary roles (Author, 2016) they need to find new ways of signalling productivity in order to move into roles that better fit upon their wider skill sets.…”
Section: Introductionmentioning
confidence: 99%
“…The strategies migrants adopt in coping with migration and precarious work have not often been the subject of research (except for Datta et al 2007;Andreotti 2006). Datta and colleagues (2007) showed that migrants in London's low-paid economy employ a range of tactics to ensure a liveable situation for 28 themselves and their relatives in London.…”
Section: Migrant Worker Practices In Dealing With Precarious Workmentioning
confidence: 99%
“…Through a moral economy perspective I explore what it is like to be a worker employed under the constraints of the European market market was liberalised (e.g. Datta et al 2007;Ryan et al 2008;Meardi 2007;Düvell and Garapich 2011;Fitzgerald and Hardy 2010;Ciupijus 2011). 20 logic and understand the effects this has on experiences of migrant employment and labour relations at the micro level (Bailey et al 2011). Inherent to markets is a tendency to disembed economic transactions from the social sphere by transforming relations of production and employment into tradable commodities (Marx 1978(Marx [1867; Polanyi 2001Polanyi [1944).…”
Section: A Moral Economy Perspective To Understand the Agency Of Labourmentioning
confidence: 99%
See 1 more Smart Citation